Who defaults during COVID-19? evidence from local lockdown restrictions - Cosma, Stefano; King, Timothy; Pennetta, Daniela (Elsevier, 2026)
We examine whether geographically heterogeneous COVID-19 lockdown restrictions affected household credit risk using a proprietary dataset of over 42,000 personal loans from an Italian financial institution. Exploiting local variation in the intensity of local lockdown restrictions, we find that stricter local restrictions significantly increased the likelihood of borrower default. The effect is heterogeneous across borrower characteristics, being stronger even among high-credit-score borrowers and attenuated for homeowners. Our results are robust to alternative specifications, including geographic exclusions of metropolitan areas. Taken together, our findings show that localized public health interventions had meaningful and uneven financial consequences, with implications for targeted credit risk and social protection policies.
Keywords: Household credit; COVID-19; Lockdowns; Default risk; Consumer finance; fi=Rahoitus|en=Finance|